Influência da estrutura da paisagem na exposição de primatas de vida livre a agentes patogênicos no Sul do Brasil - Santos, Elisandro Oliveira dos (2022)
The decline of forest ecosystems resulting from the loss and fragmentation of forest remnants is the primary reason for jeopardizing the survival of populations of wild species that depend on these environments, generating scarcity of resources, social isolation, and reduced gene flow. In addition, changes in the structure of wild habitats can provide new dynamics in the transmission of pathogenic microorganisms, expanding opportunities for exposure to various agents. In order to investigate different pathogens to which free-living primates in Rio Grande do Sul State (RS) in southern Brazil may be exposed and evaluate the relationships with the structure of the landscapes in which primates are inserted, we performed a serological survey to search for antibodies against the protozoa Leishmania infantum, Neospora caninum, Sarcocystis spp., Toxoplasma gondii, and Trypanosoma cruzi, in addition to the bacteria Brucella abortus and Leptospira spp. The samples were submitted to the serological tests of acidified antigen test (AAT), indirect hemagglutination assay (IHA-IgM/IgG), indirect fluorescence antibody test (IFAT-IgG), and microscopic agglutination test (MAT) according to the agent investigated. In addition, forest remnants were characterized in which primates were sampled in a multiscale approach in radii ranging from 200 to 1400 m using Generalized Linear Models (GLM) to investigate the potential relationship of previous exposure to agents with the elements that make up the landscape structure. In this sense, 105 blood serum samples from free-living primates were used: Alouatta caraya (63), Alouatta guariba clamitans (39), and Sapajus nigritus cucullatus (3), which were obtained between 2002 and 2016 in 48 different forest fragments. The results observed included: in the IFAT-IgG, 13% (14/105) of the samples were seropositive for N. caninum, 5% (5/105) for T. gondii, and 6% (6/105) for Sarcocystis spp. In IHA-IgM/IgG, 25% (26/105) were seropositive for T. gondii and 51% (49/96) for T. cruzi. The MAT for Leptospira spp. indicated the presence of antibodies to at least one of the 23 serogroups/serovars of the agent in 37% (37/101) of the analyzed samples. The most frequently observed serovars were: Panama (17.8%), Ballum (6%), Butembo (6%), Canicola (6%), Hardjo (5%), and Tarassovi (4%). No positive samples were observed for L. infantum and B. abortus. The metrics that best explained exposure to N. caninum, T. gondii, and Sarcocystis spp. were edges and patches density, forest cover, urban cover, and average Euclidean distance to the nearest fragment. Decreased forest cover and edge density were the landscape factors that were significantly related to exposure to Leptospira spp. A statistical association with exposure to the protozoan T. cruzi was observed in A. caraya in the Pampa biome, although no landscape metrics were related to exposure to the agent. Thus, it is possible to infer that the free-living primates in RS, A. caraya, A. g. clamitans, and S.n. cucullatus were exposed to N. caninum, T. gondii, Sarcocystis spp., Leptospira spp., and T. cruzi in the forest remnants studied. In addition, it was possible to identify that some attributes of the landscape, such as reduced forest cover, increased density of edges, and increased urban cover, are related to exposure to agents detected in the study. Thus, the results of this study open possibilities for applying the same approach to investigate shareable pathogens in habitats altered by human presence. Therefore, it contributes to management actions and establishing public policies to protect native primate species outside protected areas, which are territories in constant conflict with domestic species and anthropogenic activities.